Employee Engagement as the Key Mechanism Driving Leadership and Work-Life Balance Toward Employee Performance - Rachmawati Rachmawati; Badaruddin Badaruddin; Fitriani Latief (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This study examines the influence of leadership and work-life balance on employee performance through employee engagement as a mediating variable. The study hypothesizes that leadership and work-life balance positively affect employee engagement and employee performance, both directly and indirectly. Research Method: This study employed a quantitative approach with a causal-correlational design. Data were collected through questionnaires distributed to 100 employees selected from a population of 144 employees using simple random sampling. The research variables consisted of leadership, work-life balance, employee engagement, and employee performance. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results and Discussion: The findings indicate that leadership and work-life balance positively and significantly affect employee engagement and employee performance. Employee engagement also has a significant positive effect on employee performance. Furthermore, employee engagement significantly mediates the relationship between leadership and employee performance, as well as between work-life balance and employee performance. Implications: The findings emphasize the importance of strengthening leadership quality and implementing work-life balance policies to improve employee engagement and organizational performance in the financial service industry. Originality: This study integrates the Job Demands-Resources Model and Social Exchange Theory by positioning employee engagement as a mediating mechanism in the multifinance industry, a gap noted in previous studies.